Evaluation of Hematological and Biochemical Alterations Induced by Non-selective Cyclooxygenase Inhibitors (Piroxicam) in Rabbits - Warida El-Rwegi; Amer Elgerwi; Aisha Zaidi; Wafa Elmghirbi; Afaf El-Nass; Abubaker El-Mahmoudy (African Journal of Advanced Pure and Applied Sciences, 2024)
Piroxicam is a nonsteroidal anti-inflammatory drug (NSAID) recommended for various medical conditions. Conversely, piroxicam’s hemato-biochemical and hepato-renal-induced toxic effects have been reported. Therefore, the present study aimed to evaluate the impact of piroxicam on some hematological and biochemical parameters in rabbits and examine the histological changes in the kidney and liver. Eighteen adult male New Zealand rabbits weighing (1800-2000 grams) were used in this study and randomly distributed into three groups (n=6). Group 1 is considered as a control. The second and third groups were intramuscularly treated for five consecutive days with concentrations (1, 2) mg/kg of piroxicam respectively. After 5 days blood samples were collected and used for hematological and biochemical analysis. Then, animals were sacrificed; their kidneys and livers were removed and processed for histological examination. High-dose piroxicam significantly (P ≤ 0.05) decreased red blood cell count, hemoglobin, hematocrit, mean corpuscular hemoglobin, mean corpuscular hemoglobin concentration, and White blood cells compared to the control group. Additionally, Piroxicam high dose significantly (P ≤ 0.05) elevated the serum levels of AST, ALT, urea, creatinine, and uric acid, while decreased levels of triglycerides, and glucose significantly (P ≤ 0.05) compared to the control. Histopathological examination revealed a dose-dependent piroxicam-induced renal damage, including, cortical blood vessel dilatation, tubular necrosis, glomerular tuft swelling, and interstitial inflammation. Similar dose-dependent effects were observed in liver tissues exhibiting hydropic and ballooning hepatocyte degeneration. The present study demonstrated that piroxicam induced significant hematological, biochemical, and hepato-renal histological alterations in rabbits.